Penerapan Total Productive Maintenance (TPM) Pada Mesin Building RTBC1 Di PT ASWX - Wijaya, Astika Sari; Wahyudi, Rizqi (Jurnal Ilmiah Teknologi dan Rekayasa, 2025)
The RTBC1 machine is a building machine used to combine tire components. The problem in this study is that the current condition of the RTBC1 building machine is not yet in a suitable condition to operate effectively. The cause is that there is output from the machine that experiences damage (downtime) and disruptions to the machine due to machine components experiencing problems that impact the speed of machine production. This study aims to analyze the most dominant factors of the Six Big Losses, the implementation of Total Productive Maintenance (TPM) and Maintenance, Repair, and Overhaul (MRO), and provide recommendations for continuous improvement from the results of TPM implementation. The initial research results obtained that the OEE value of the RTBC1 machine is 78% and is still below the international standard (≥85%). After the initial improvement recommendations using one of the TPM pillars, namely autonomous maintenance, a change in the machine's OEE value was obtained, which increased by 5.1% to 83.1%. However, this only slightly reduced the value of losses, there are still two dominant losses, namely reduced speed losses with a value of 20.78% and idling and minor stoppages losses with a value of 14%. The improvement recommendations given to reduce these two losses are to use one of the MRO actions, namely running maintenance.